Students’ Metacognitive Processes in Mathematical Problem Solving Viewed from VARK Learning Styles - Yanti, Aning Wida; Alvira, Rahma (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2026)
Metacognition plays a crucial role in enhancing students’ problem-solving abilities through the processes of planning, monitoring, and evaluation, enabling more systematic and effective thinking. In addition, students’ learning styles influence how metacognitive processes are applied in solving mathematical problems. Understanding these processes allows teachers to design instructional strategies that align with students’ characteristics. This study aims to describe students’ metacognitive processes in solving mathematical problems based on VARK learning styles. A qualitative case study approach was employed involving eight tenth-grade students of MAN 2 Kota Kediri, with two students representing each learning style identified through the VARK questionnaire. Data were collected using problem-solving tests and semi-structured interviews, then analyzed through data condensation, data display, and conclusion drawing, with source triangulation ensuring validity. The findings reveal that visual and read/write learners demonstrate more consistent performance in understanding problems and applying strategies, although evaluation is sometimes incomplete. Auditory and kinesthetic learners tend to rely on previously learned strategies but show less consistency in monitoring and evaluating their solutions. All students exhibit confidence in their approaches based on prior experiences. Further research is recommended to explore metacognitive processes using more diverse problem types.